Antimicrobial-resistant CC17 Enterococcus faecium: The past, the present and the future. (March 2019) - Lee, Terence; Pang, Stanley; Abraham, Sam; Coombs, Geoffrey W.
Highlights: CC17 Enterococcus faecium has emerged as a pandemic clone. Vancomycin resistance is a critical issue. Dissemination of CC17 E. faecium in the human–animal–environment interface has been documented. Current epidemiology of vancomycin-resistant E. faecium. Therapeutic alternatives to vancomycin for vancomycin-resistant CC17 E. faecium. Abstract: Enterococcus faecium is a robust opportunistic pathogen that is most commonly found as a commensal of the human and animal gut but can also survive in the environment. Since the introduction and use of antimicrobials, E. faecium has been found to rapidly acquire resistance genes that, when expressed, can effectively circumvent the effects of most antimicrobials. The rapid acquisition of multiple antimicrobial resistances has led to the adaptation of specific E. faecium clones in the hospital environment, collectively known as clonal complex 17 (CC17). CC17 E. faecium are responsible for a significant proportion of hospital-associated infections, which can cause severe morbidity and mortality. Here we review the history of E. faecium from commensal to a significant hospital-associated pathogen, its robust phenotypic characteristics, commonly used laboratory typing schemes, and antimicrobial resistances with a focus on vancomycin and its associated mechanism of resistance. Finally, we review the global epidemiology of vancomycin-resistant E. faecium and potential solutions to problems faced in public health.